Biocompatible and Biodegradable Organic Transistors Using a Solid‐State Electrolyte Incorporated with Choline‐Based Ionic Liquid and Polysaccharide. (4th February 2020) - Jo, Young Jin; Kim, Heyn; Ok, Jehyung; Shin, Yiel‐Jae; Shin, Joo Hwan; Kim, Tae Hee; Jung, Youngmee; Kim, Tae‐il
Abstract: Biocompatible, biodegradable, and solid‐state electrolyte‐based organic transistors are demonstrated. As the electrolyte is composed of all edible materials, which are levan polysaccharide and choline‐based ionic liquid, the organic transistor fabricated on the electrolyte can be biocompatible and biodegrable. Compared to the other ion gel based electrolytes, it has superior electrical and mechanical properties, large specific capacitance (≈40 µF cm −2 ), non‐volatility, flexibility, and high transparency. Thus, it shows mechanical reliability by maintaining electrical performances under up to 1.11% of effective bending strain, 5% of stretching, and have low operation voltage range when it is utilized in organic transistors. Moreover, the biodegradable electrolyte‐based organic transistors can be applied to bio‐integrated devices, such as electrocardiogram (ECG) recordings on human skin and the heart of a rat. The measured ECG signals from the transistors, compared to signals from electrode‐based sensors, has a superior signal‐to‐noise ratio. The biocompatible and biodegradable materials and devices can contribute to the development of many bioelectronics. Abstract : Biocompatible and biodegradable organic transistors are fabricated by using a solid‐state electrolyte composed of choline‐based ionic liquid and polysaccharide. This electrolyte can serve as both the dielectrics and the substrate of the electronics. This biocompatible and biodegradable organic transistor can be a promising component of bio‐integrated electronics as applied to recording bio‐signals.